Bridging the Gap : Identifying What is Holding Self-Employed Women Back in Ghana, Rwanda, Tanzania, the Republic of Congo, and Uganda - Nix, Emily (World Bank, Washington, DC, 2014)
This paper explores the determinants of the gender gap in income earnings in five Sub-Saharan countries: the Republic of Congo, Ghana, Rwanda, Uganda, and Tanzania. It shows that first, self-employment tends to provide marginally lower average income (with the exception of Ghana and men in Rwanda) and much higher variability in income compared with wage work. Women on average earn less than men when they are self-employed and in wage employment, but also have less volatile earnings. The analysis uses quantile decomposition methods and finds that the differences in observable choices and endowments explain the gender gap in earnings for the self-employed who earn the least while the gap for the most successful male and female entrepreneurs is largely driven by differences in returns to observable covariates in the majority of the countries. These results suggest a glass ceiling effect, wherein a large portion of the income gaps between high-earning men and women cannot be explained by observable characteristics. The paper concludes by looking at the variables that account for a larger portion of the gender gap explained by observable characteristics and finds that hours of work and industry explain a higher fraction compared with standard human capital and demographic factors such as age and education.